Análise da influência da resistência à compressão de diferentes concretos na aderência com a armadura - Martins, Tamiris Evangelista (2016)
In recent decades, concrete has become the most commonly used material in construction. The reinforced concrete, study object of this work, is a concrete structure which has a reinforcement with steel bars inside. Its function is to resist the compressive forces and the steel function is to resist tensile. Compliance is responsible for ensuring that these two distinct elements, concrete and steel, work together to resist the efforts to which they are requested. This work aims to analyze the influence of the strength of concrete compression gives the grip of steel-concrete set. Realizing the pull-out-test, which is characterized by a tensile test. The special concretes SCC, HPC and RPC have a better selection of materials, limiting the size of the coarse aggregate, used additives and compounds which cause the amount of voids in the concrete structure are much smaller than conventional concretes. Therefore these special concretes have a greater resistance to compression than conventional one, analogously greater compressive strength results in higher bondstrength.